The Improvement of Student Learning Activity Using the Problem Based Learning (PBL) Model Assisted by Smartbox Media in Grade VI at SDN 97/VI Kota Jambi - Maharani Putri Rahayu; Lela Rahmawati; Annisa Rahmawati Siregar; Ardi Nur Hanafi; Aprilia Widiastuti (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
The aim of this study is to improve the learning activity of grade VI students at SDN 97/IV Kota Jambi through the Problem Based Learning (PBL) model assisted by the SmartBox media. This research applies the Classroom Action Research (CAR) method, which is implemented in two cycles, consisting of planning, implementation, observation, and reflection stages. Data collection was carried out through interviews, observations, and document analysis, with indicators of activity including student participation in tasks, discussions, and problem-solving. The results of the study show that the implementation of PBL assisted by SmartBox is effective in increasing learning activity. In the pre-cycle, student activity reached only 32%, while in the second cycle, the second meeting showed an improvement to 84%. The combination of PBL and SmartBox created an interactive and effective learning environment that encouraged students to be more active, creative, and engaged in the learning process. This study concludes that PBL assisted by SmartBox is a relevant approach to enhance student activity and learning outcomes, especially in the IPAS subject.